Relationships Between Distention-, Butyrate- and Pellet-Induced Stimulation of Peristalsis in the Mouse Colon - Tan, Wei; Lee, Grace; Chen, Ji-Hong; Huizinga, Jan D. (Frontiers in Physiology, 2020)
Luminal factors such as short-chain fatty acids are increasingly recognized for playing a regulatory role in peristaltic activity. Our objective was to understand the roles of butyrate and propionate in regulating peristaltic activity in relation to distention-induced activities. Butyrate and propionate were perfused intraluminally under varying outflow pressures to murine colons bathed in Krebs's solution. We used video recording and spatiotemporal maps to examine peristalsis induced by the intrinsic rhythmic colonic motor complex as well as the pellet-induced peristaltic reflex. Our results show that the cyclic motor complex showed several configurations at different levels of excitation, culminating in long-distance contractions which possess a triangular shape in murine colon spatiotemporal maps. Butyrate increased the frequency of cyclic motor patterns but was a much weaker stimulus than distention and only contributed to significant changes under low distention. Propionate inhibited cyclic motor patterns by decreasing either their amplitudes or frequencies, but only in low distention conditions. Butyrate did not consistently counteract propionate-induced inhibition likely due to the multiple and distinct mechanisms of action for signalling molecules in the lumen. Pellet movement occurred through ongoing cyclic motor patterns and pellet induced peristaltic reflexes. Butyrate augmented both colonic motor complexes and peristaltic reflexes to decrease the amount of time required to expel each pellet. In conclusion, butyrate is effective in promoting peristalsis, but only when the initial level of colonic activity is low. This suggests that it may play a significant role in patients with poor fiber intake, where there is low mechanical stimulation in the lumen.